Photo- and redox-regulated transmembrane ion transporters - Ahmad, M; Gartland, SA; Langton, MJ (Wiley, 2023)
Synthetic supramolecular ion transporters find applications as potential therapeutics and as tools for engineering functional membranes. Stimuli-responsive systems enable external control over transport, which is necessary for targeted activation. The Minireview provides an overview of current approaches to developing stimuli-responsive ion transport systems, including channels and mobile carriers, that can be controlled using photo or redox inputs.